REVIEW OF IMPLEMENTATION OF GOVERNMENT AUTHORITIES IN POLICY-MAKING IN THE "RELIGIOUS AFFAIRS" - Abadi, Husnu; Ibnususilo, Efendi; Rahdiansyah, Rahdiansyah (Tadulako Law Review, 2018)
Government absolute authorities in the religion affairs is the authority of the central government. In the dynamic development of political, many district that produce regional policy with respect to religion or to follow religious aspirations of local people. Some districts in Riau Province, a county division during the reform, including the district are very concerned about the development in the field of religion. In addition to physical development, the county authority also extend its authority in the religion affairs. Regional policy is embodied in the form of local laws, regulations regent, or Medium Term Development Plan (Plan) Government District in Riau Province. This is possible because there are no clear boundaries of understanding in the rule of religion affairsÂ  formulated by the law on local government. The central government, based on this study, it gives tacit consent when local governments do just that, because the rate it is going to add a lot of partners in the central government district. There is no struggle for power between central government and local governments, but the expansion of the district authority in religious issues involved in managing the government's response is a manifestation of the district in the religious aspirations of the people of the area